Learning Outcomes for Economists - Allgood, Sam; Bayer, Amanda (American Economic Review, 2017)
Articulating thoughtful learning outcome statements for courses and majors improves teaching and learning and satisfies accreditation requirements. After reading this paper, economists will be able to construct learning outcome statements that guide and enhance teaching and learning in their courses and programs. We present a framework for developing learning outcomes based on a set of five fundamental competencies in economics. We then provide another public good, offering a complete set of learning outcomes for an introductory microeconomics course, which instructors can include in their syllabi. For additional guidance, we construct examples of lesson-specific learning outcomes as well.